The evolution of repressive policies of the Bolsheviks in 1920–1924 on the example of Kuban-Black Sea region - Maria S. Dirivyankina (Кавказология, 2024)
The change of power in October 1917 in Russia led to an increase in confrontation in society, expressed both in an open military conflict - the Civil War, and in the growth of political radicalism. Any government in relation to its opponents - in this case, counter-revolutionaries, conspirators, rebels - reserves the right to use legal violence, which reflects one of the main functions of the state. The problem of red terror, like white terror, in turn, is at the intersection of the concepts of law and lawlessness, since they were carried out by the state in the form of lynchings and reprisals, which included innocent citizens. The V All-Russian Congress of Soviets ensured the legalization of the legal policy of the Bolsheviks. The regime of power established in October 1917 passed into the status of legitimate, and the formed state bodies received the right to legally implement all functions available to the state, including receiving a monopoly on violence. The problems of the transition period from war communism to NEP, accompanied by extra-legal methods, manifested themselves most clearly in the Cossack south of Soviet Russia, which differed in class, national composition and special land use conditions.